Elaboración de una guía de aves del campus Salache de La Universidad Técnica De Cotopaxi del Cantón Latacunga provincia de Cotopaxi - Casacumba Panchi, Luis Hernán (2024)
The main objective of this research is to prepare a descriptive guide of birds in the Salache campus in the canton of Latacunga, province of Cotopaxi, in order to collect information on as many species as possible. In the first objective, a situational diagnosis was made with the pertinent bibliographic review of web pages, books, magazines and scientific articles. In the second objective, the birds on the Salache campus were inventoried. For this research process, techniques and tools were established that facilitated the research process, such as: field notebooks for the identification of the species recorded, and the following tools were used: camera, GPS and binoculars. The research process was carried out using techniques such as: line transects, direct observations and intensive search. The realization of field trips were 5 in total, where it was possible to know the study area which later was known the physical characteristics of the site, with this it was possible to determine what could be the most suitable spaces within the faculty of CAREN for monitoring birds, mainly taking into account the characteristics such as the number or presence of individuals of different species in each space, so it was possible to establish three areas for bird watching, which were: the area of the hacienda where about 8 different species of birds could be seen, the area of crops where agronomy students perform their practices with short-cycle crops where 9 species of birds different from the first zone were found and the third zone in the campus field where 23 species different from the first and second zone were found. Taking this into account, a route was traced linking all the areas established for monitoring and using the technique of direct observation, with the objective of observing and photographing the species found along the route. And as a third objective, we proceeded to systematize the information obtained to subsequently select the photographs taken of the species, which allowed their identification with the help of the guide Birds of Ecuador volume 1 and Fieldbook of the Birds of Ecuador where we were able to classify the species recorded, which later served for the realization of the bird guide through the canva.